Chronic cholecystitis: Diagnostic and therapeutic insights from formerly bile-farmed Asiatic black bears (Ursus thibetanus). - Szilvia K Kalogeropoulu; Emily J Lloyd; Hanna Rauch; Irene Redtenbacher; Michael Häfner; Iwan A Burgener; Johanna Painer-Gigler (PLoS ONE)
Across Southeast Asia and China, more than 17000 Asian bears are kept under suboptimal conditions and farmed for their bile to meet the consumer demand for traditional medicine products. Years of unsterile and repetitive bile extraction contribute to the development of chronic sterile or bacterial cholecystitis, a pathology commonly diagnosed in formerly bile-farmed bears. In both human and veterinary medicine, the diagnostic value of the macroscopic bile examination for assessing gallbladder disease is unclear. The objective of this study is to identify the role of gallbladder bile color, viscosity, and turbidity, while comparing them with established markers of cholecystitis. Moreover, it aims to define the optimal duration of oral antibiotic treatment for chronic bacterial cholecystitis in bears associated with bile farming. Thirty-nine adult, formerly bile-farmed Asiatic black bears (Ursus thibetanus) were examined under anesthesia and underwent percutaneous ultrasound guided cholecystocentesis. A total of 59 bile samples were collected with 20 animals sampled twice to evaluate the therapeutic success. All bile aspirates were assessed macroscopically and microscopically followed by submission for bacterial culture and antimicrobial sensitivity. In the majority of bears, samples with cytological evidence of bactibilia lacked inflammatory cells and did not always correlate with positive bacterial cultures. The most common bacterial isolates were Enterococcus spp, Streptococcus spp and Escherichia coli. Based on our findings, the optimal duration of antibiotic treatment for chronic bacterial cholecystitis is 30 days. Moreover, unlike Gamma-glutamyl Transferase (GGT) and gallbladder wall thickness, the organoleptic properties of bile were found to be reliable markers of chronic gallbladder inflammation with color and turbidity indicating cholestasis. The current study highlights the importance of cholecystocentesis for the management of gallbladder disease and provides initial results on the possible diagnostic value of macroscopic bile examination.